Pengaruh Pupuk Organik dan Intensitas Naungan terhadap Pertumbuhan Bibit Kopi Robusta (Coffee canephora Pierre ex Froehner) - Ade Wachjar; Yadi Setiadi; Lies Wahyuni Mardhikanto (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2002)
The experiment was aimed at study the effect of organic fertilizer and shading inetnsity on yhe growth of Robusta coffee seedling. Seven month old seedling of hybrid variety of BP 42 and BP 358 crossing were used in the experiment was conducted at Cikabayan Experimental Station Bogor Agriculture University, from July 2000 to January 2001. The experiment was arranged in split plot dessign with three replications. the main plot was shading intensity cinsisted of 25% (N1), 50% (N2), 75% (N3), and 100% (N4) shade. The sub plot was organic fertilizer consisting of 4 g EMAS + 1/2 dosage of inorganic fertilizier (d.i.f), 4 ml EM4 + 1/2 d.i.f (P2), 4 g OST + 1/2 d.i.f(P3), 20 ml Soils Plus + 1/2 d.i.f(P4) and 1 dosage of inorganic fertilizer (P5). Organic fertilizer affected growth, as shown by height and stem diameter of seedling at early period of experiment and shoot biomass at the end of experiment compared to one effect on all variable during the experiment. Keyword : Coffee, Shading, Oerganic fertilizer